2008
DOI: 10.1590/s0103-84782009005000072
|View full text |Cite
|
Sign up to set email alerts
|

Fluxo de tecido foliar em azevém anual manejado sob três intensidades de pastejo

Abstract: O fluxo de tecido foliar de azevém (Lolium multiflorum Lam.) foi quantificado sob três intensidades de pastejo. As intensidades corresponderam ao desaparecimento de 21,1 ("Baixa"); 43,3 ("Média") e 61,0% ("Alta") do valor da matéria seca total inicial em cada ciclo de pastejo. Os animais experimentais utilizados foram cordeiras, e a soma térmica de 313 graus-dia determinou o intervalo entre pastejos. O delineamento experimental foi inteiramente casualizado com três tratamentos e quatro repetições. Na intensida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…To understand the effects of different types of management strategies on pasture dynamics and evolution, knowledge of the growth, intake, and senescence of forage species is fundamental. Thus, determination of these parameters through biomass flow technique is fundamental for the understanding of pasture ecophysiology (CONFORTIN et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the effects of different types of management strategies on pasture dynamics and evolution, knowledge of the growth, intake, and senescence of forage species is fundamental. Thus, determination of these parameters through biomass flow technique is fundamental for the understanding of pasture ecophysiology (CONFORTIN et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While comparing methods (rotational and continuous) and two grazing intensities (low and moderate), CAUDURO et al (2007) verified that rotational stocking and low intensity favored growth flow and in continuous stocking with low defoliation intensity, the senescence rate was increased. In a study on ryegrass managed under three forage disappearance intensities, CONFORTIN et al (2009) observed that in grazing, the 43.3% disappearance intensity of pre-grazing forage mass allowed a greater flow of leaf blades intake, with intermediate growth and senescence flows. SILVA et al (2015), observed that when ryegrass is managed under different stocking rates, the leaf biomass flow is not altered.…”
Section: Introductionmentioning
confidence: 99%
“…has been extensively studied due to its importance for livestock production systems in southern Brazil (CONFORTIN et al, 2010(CONFORTIN et al, , 2013BANDINELLI, 2005), and studies on biomass flows have been performed for both tropical (CUTRIM JUNIOR et al, 2013;LOPES et al, 2013) and temperate species such as ryegrass (CAUDURO et al, 2007;CONFORTIN et al, 2009;PONTES et al, 2004). However, no studies have been published on the flows of leaf biomass at high stocking rates as a result of intake of different supplements by cattle.…”
Section: Introductionmentioning
confidence: 99%
“…is the most studied temperate species, with studies in several research areas (ROMAN et al, 2007; Acta Scientiarum. Animal Sciences Maringá, v. 36, n. 3, p. 279-283, July-Sept., 2014 CONFORTIN et al, 2009;ROSO et al, 2009;ROSA et al, 2013). Tiller dynamics is extensively studied with tropical species (DIFANTE et al, 2008;FIALHO et al, 2012;ZANINE et al, 2013).…”
Section: Introductionmentioning
confidence: 99%